A water-soluble Cu complex as molecular catalyst for electrocatalytic CO2 reduction on graphene-based electrodes - Wang, Jiong (2020)
A structurally simple molecular 1,10‐phenanthroline‐Cu complex on a mesostructured graphene matrix that can be active and selective toward CO2 reduction over H2 evolution in an aqueous solution is reported. The active sites consist of Cu(I) center in a distorted trigonal bipyramidal geometry, which enables the adsorption of CO2 with η1‐COO‐like configuration to commence the catalysis, with a turnover frequency of ≈45 s−1 at −1 V versus reversible hydrogen electrode. Using in situ infrared spectroelectrochemical investigation, it is demonstrated that the Cu complex can be reversibly heterogenized near the graphene surface via potential control. An increase of electron density in the complex is observed as a result of the interaction from the electric field, which further tunes the electron distribution in the neighboring CO2. It is also found that the mesostructure of graphene matrix favored CO2 reduction on the Cu center over hydrogen evolution by limiting mass transport from the bulk solution to the electrode surface.